Impact of Parental Education and Employment on households’ food security in Pakistan: Application of Bayesian Logistic Framework - Muhammad, Akbar; Amjad , Muhammad; Iqbal , Zahid (Progress in Nutrition, 2021)
This study evaluates the role of some important socioeconomic factors including parental education and employment on households’ food security in Pakistan using Bayesian logit model. Cross sectional data of 14948 households from national surveys, i.e. HIES 2013-14 (Prior information) and HIECS 2015-16 (Current data), are extracted. Food security status is determined by calculating difference between daily per adult capita calories consumption and requirement for each household. Sample data shows that 58% of the households are food insecure which reveals the worst situation of food security in Pakistan. The model is estimated using Bayesian logistic framework. The study concludes that maternal and paternal paid employment and other parental employment are effective to improve food security status in Pakistan. Adverse impact of dependency ratio also induces creation of employment opportunities, especially for lower class families. However, couple employment shows insignificant impact on food security due to probably time constraints. Agricultural employment seems to be the most effective factor to fulfill calories requirement at household level. Insignificance of maternal as well paternal primary and middle education where as significant positive role of high parental education is observed which may be attributed to awareness of food security through education. It induces policy steps to raise level of education rather than literacy rate. Moreover, the analysis shows that the rural areas compared to urban areas and Baluchistan compared to other provinces are facing the worst conditions of food insecurity. Development of agricultural sector, creation of employment opportunities to control unemployment, raising level of parental education rather than literacy rate and introduction of developmental and social welfare schemes for backward areas are some important guidelines for food security policy of Pakistan in order to chase the Vision 2050 of UNO.